Dispersion relation equation of shallowwater: wavelength estimator / Nor Azni Shahari ... [et al.] - Shahari, Nor Azni (UiTM Cawangan Negeri Sembilan, 2022)
Waves are a familiar occurrence on the ocean and may be observed on nearly any water surface that is exposed to the atmosphere. Water waves are generated by wind blowing over the water surface, it may also be caused by air pressure disturbances, flow obstructions, landslides, or literally anything else that disrupts the water surface. Waves may be characterized by a wave height, H, and wavelength, L. A wave height, H is defined as the elevation difference between the wave crest and wave trough, and a wavelength, L, which is the horizontal distance between successive crests or troughs as illustrated in Figure 1 (Kennedy, 2019). Waves will also have a period, T, which is defined as the time for successive crests or troughs to pass a fixed point. The study of water waves has been crucial for both theoretically and practically in domains ranging from mathematical sciences to coastal facility design and harbor structures, ecological networks, and tsunami and storm inundation prevention.